2014
DOI: 10.1007/s40268-014-0048-6
|View full text |Cite
|
Sign up to set email alerts
|

Medium-Term Effects of Insulin Degludec on Patients with Type 1 Diabetes Mellitus

Abstract: ObjectiveThe aim of this study was to analyze the changes in daily blood glucose fluctuation and insulin dose in patients with type 1 diabetes mellitus (T1DM) undergoing basal-bolus therapy following a switching of basal insulin used from insulin glargine or detemir to insulin degludec.MethodsSeven patients with T1DM were enrolled. All patients treated with insulin glargine or detemir twice daily were switched to insulin degludec with 80–90 % of the prior insulin dose. During the study period, the basal insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
1
4
3
Order By: Relevance
“…Consistent with our findings, patients required a lower daily dose of Deg compared to their prior insulin dose and the required dose of basal insulin decreased significantly 24 weeks after switching. However, the improvement in MAGE that we report here was not observed in this previous study [10]. The reason for the discrepancy in CGM data is unclear, but may be due to the differences in the number of participants or the inclusion of hospitalized patients in the current study whose diet and activity were closely monitored.…”
Section: Insulin Dose (Table 2)contrasting
confidence: 84%
See 2 more Smart Citations
“…Consistent with our findings, patients required a lower daily dose of Deg compared to their prior insulin dose and the required dose of basal insulin decreased significantly 24 weeks after switching. However, the improvement in MAGE that we report here was not observed in this previous study [10]. The reason for the discrepancy in CGM data is unclear, but may be due to the differences in the number of participants or the inclusion of hospitalized patients in the current study whose diet and activity were closely monitored.…”
Section: Insulin Dose (Table 2)contrasting
confidence: 84%
“…Recently, the same group has published two reports assessing the effects of Deg and Gla using CGM with a test diet [9,10]. Patients with type 1 diabetes were switched from Gla or detemir to Deg and followed for 12 or 24 weeks.…”
Section: Insulin Dose (Table 2)mentioning
confidence: 99%
See 1 more Smart Citation
“…After switching, the glycemic control was improved in all types of patients. In previous studies 7,9 , when participants were switched to IDeg, the basal insulin dose was adjusted, and dose reduction was greater in these reports than in the present study. Such greater dose reduction might be one of the reasons for unimproved glycemic control for participants that switched to IDeg in the previous studies 7,9 .…”
Section: Discussioncontrasting
confidence: 47%
“…In previous studies 7,9 , when participants were switched to IDeg, the basal insulin dose was adjusted, and dose reduction was greater in these reports than in the present study. Such greater dose reduction might be one of the reasons for unimproved glycemic control for participants that switched to IDeg in the previous studies 7,9 . Therefore, our finding suggested that smaller basal insulin dose reduction might provide better glycemic control when patients with difficult glycemic control using IGlar or IDet were transferred to IDeg.…”
Section: Discussioncontrasting
confidence: 47%